2019
DOI: 10.1007/s00401-019-02040-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for bidirectional and trans-synaptic parasympathetic and sympathetic propagation of alpha-synuclein in rats

Abstract: The conversion of endogenous alpha-synuclein (asyn) to pathological asyn-enriched aggregates is a hallmark of Parkinson’s disease (PD). These inclusions can be detected in the central and enteric nervous system (ENS). Moreover, gastrointestinal symptoms can appear up to 20 years before the diagnosis of PD. The dual-hit hypothesis posits that pathological asyn aggregation starts in the ENS, and retrogradely spreads to the brain. In this study, we tested this hypothesis by directly injecting preformed asyn fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
175
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(198 citation statements)
references
References 56 publications
13
175
1
Order By: Relevance
“…In a recent study, we performed injections with preformed asyn fibrils into the duodenum of transgenic rats, which overexpress human full-length wild-type asyn (Fig. 5) [71]. At 2-and 4 months postinjection, we detected very robust propagation of asyn pathology via the vagus nerve to the DMV, and via the sympathetic connectome to the coeliac ganglion and the intermediolateral cell column (IML).…”
Section: Evidence From Animal Studiesmentioning
confidence: 89%
“…In a recent study, we performed injections with preformed asyn fibrils into the duodenum of transgenic rats, which overexpress human full-length wild-type asyn (Fig. 5) [71]. At 2-and 4 months postinjection, we detected very robust propagation of asyn pathology via the vagus nerve to the DMV, and via the sympathetic connectome to the coeliac ganglion and the intermediolateral cell column (IML).…”
Section: Evidence From Animal Studiesmentioning
confidence: 89%
“…In a recent publication, Van den Berge et al, (13) showed that alpha-synuclein PFF seeds injected into the duodenum wall of a transgenic rat model induce an alpha-synuclein pathology which propagates transynaptically and bidirectionally through the parasympathetic and sympathetic nervous system to the brain stem in a pattern which recapitulates Braak's hypothesis (6) of the development of a patterned pathological propagation in PD. This finding, together with the seminal demonstration of PFF induced pathology propagating from the gastrointestinal tract to the brains in rats (11), strengthens the growing suspicion of idiopathic PD originating from a yet unidentified pathogen capable of passing the mucosal barrier (84).…”
Section: Induction Of Pathology By Alpha-synuclein Pff Seedsmentioning
confidence: 81%
“…Focusing on the second most common neurodegenerative disease, PD, the implicated proteinopathy mainly consists of misfolded and aggregated forms of alphasynuclein. These intracellular alpha-synuclein inclusions are termed Lewy bodies or Lewy neurites, and can be found propagating throughout central, peripheral and autonomic parts of the nervous system, as well as in multiple organs, as the disease progresses (6,7,(10)(11)(12)(13)(14). Furthermore, the neurodegenerative process characteristic of PD particularly affects and progressively depletes the dopaminergic neurons in the substantia nigra pars compacta (SNpc), a process which is thought to underlie most of the movement-related symptoms (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…van IJzendoorn and P. Derkinderen / Intestinal Barrier in PD S327 lowing their injection into the mouse muscularis layer of the pylori and duodenum but not when the mice were subjected to truncal vagotomy following alpha-synuclein fibril injection. Finally, also in a bacterial artificial chromosome transgenic rat model that overexpressed the human alpha-synuclein encoding gene, gut-to-brain propagation of injected alpha-synuclein fibrils via the vagus nerve was demonstrated [20]. Conceivably, the Braak model requires that the intestinal epithelial barrier should be porous enough to give way to a hitherto unknown neurotropic pathogen to trigger alpha-synuclein misfolding and aggregation in the nearby enteric neurons [21].…”
Section: How Could a Compromised Intestinal Barrier Function Contribumentioning
confidence: 99%